(untitled) (Discourse of Law and Administration, 2025)
The article presents the activities and powers of the prosecutor in administrative proceedings. The conducted considerations lead to the conclusion that the powers granted serve to implement the principle of a fair trial and the rule of law. Therefore, the procedural role of the prosecutor in the light of the powers he has is important, although sometimes marginalized. The purpose of this study is to characterize the prosecutor’s activity at various stages of administrative proceedings and to try to answer the question whether these activities have a real impact on the process.